Examining the role of spatial skills and mathematics motivation on middle school mathematics achievement - Kinnari Atit; Jason R. Power; Norma Veurink; David H. Uttal; Sheryl Sorby; Grace Panther; Camille Msall; Logan Fiorella; Martha Carr (SpringerOpen, 2020)
Abstract Background Spatial skills and mathematical ability have been repeatedly identified as critical for achievement in Science, Technology, Engineering, and Mathematics (STEM). Previous studies have identified correlations between spatial skills and mathematical achievement; however, questions remain regarding improvements in non-spatial areas associated with STEM achievement. The current study examined whether competency in spatial skills could be related to individuals' motivation for mathematics. Measures of spatial skills and mathematics motivation were completed by 1056 seventh grade students. Results Using hierarchical linear modeling, spatial skills and math motivation were examined relative to students' performance on a state standardized mathematics subtest. Results indicate that spatial skills and motivation interact to significantly predict students' mathematics performance. Conclusions These results suggest that spatial skills in combination with motivation play a significant role in middle school students' mathematics achievement.